ChemInform Abstract: From QCA (Quantum Cellular Automata) to Organocatalytic Reactions with Stabilized Carbenium Ions. Issue 32 (July 2016) - Gualandi, Andrea; Mengozzi, Luca; Manoni, Elisabetta; Cozzi, Pier Giorgio
Abstract: Review: [119 refs.